Studi Bibliometrika Jurnal Teknologi Dirgantara (JTD) Dan Jurnal Sains Dirgantara (JSD) Periode 2017-2021 - Rochani Rahayu; Ainun Zakiah Noor Noor (Perpustakaan Universitas Riau, 2022)
Until now there has been no research on the characteristics of JTD and JSD, so the research was carried out. Bibliometric methods are used, with data sources being JTD and JSD accessed from the site: http://jurnal.lapan.go.id. Specifically the study aims to find out: 1) The number of articles during 2017 – 2021; 2) Authorship patterns and degrees of collaboration; 3) The number of references used; 4) Gender; 5) The most prolific writer; 6) The institution where the author works; 7) The most keywords appear. Based on the results of the study, it was concluded that in JTD, during 2017 - 2021, 85 articles were published, written by 145 male authors (83.82%), and 27 women (15.61%). References per article are 16.30 titles/published articles. The author collaboration degree value is 0.85. Authors from ITB and LAPAN are in the first position . The most prolific author is M.Giri Suada with 11 articles. The most common keywords are Finite element method, landing gear and CFD, each appearing 4 times. In JSD the number of articles published is 45 titles, written by 70 male authors (65.42%), and 37 women (34.58%), with the average number of references / articles is 19.62 titles, the most productive author is Rhorom Priyantikanto, with the number of writings 7 titles. The JSD collaboration degree is 0.84. The most keywords are Geomagnetic storm. It is generally concluded that in both journals the number of male authors is dominant compared to women, articles written collaboratively more than articles written individually, and the institutions that contribute the most are ITB and LAPAN. Kyoto University, Technische University of Munich, University of Adelaide is an overseas university that contributes to both journals